2018
DOI: 10.31513/linguistica.2018.v14n2a17542
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual categorization of English vowels by native European Portuguese speakers

Abstract: This study reports the results of a perceptual assimilation task (PAT) used to assess the degree of perceived cross-language (dis)similarity between the vowel inventories of European Portuguese (L1) and American English (L2) and, thus, predict difficulty in the perception and production of non-native vowels. Thirty-four native European Portuguese speakers completed a PAT, in which they mapped both L2 English and L1 Portuguese vowels to native vowel categories and rated them for goodness-of-fit to L1 vowels. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…It is also a valuable contribution for the SLM and for the development of theoretical insights into the relationship of perception and production in speech processing more generally. Within months of the conclusion of our exhaustive literature search for this meta-analysis, two more studies, Inceoglu (2014) and Rato (2013), were published that would have passed the inclusion and exclusion criteria. Both of these studies targeted L2 vowels and the effect sizes of production scores after perception training was consistent with the findings of this meta-analysis 9 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also a valuable contribution for the SLM and for the development of theoretical insights into the relationship of perception and production in speech processing more generally. Within months of the conclusion of our exhaustive literature search for this meta-analysis, two more studies, Inceoglu (2014) and Rato (2013), were published that would have passed the inclusion and exclusion criteria. Both of these studies targeted L2 vowels and the effect sizes of production scores after perception training was consistent with the findings of this meta-analysis 9 .…”
Section: Resultsmentioning
confidence: 99%
“… 9. Inceoglu (2014) trained two groups of participants, and the effect of perception training on production was d = 0.30 and 0.16. Rato (2013) trained one group, and the effect was d = 0.38. …”
Section: Notesmentioning
confidence: 99%
“…The predicted challenges in the perception of the target English vowels were determined by previous research with L2 European Portuguese speakers, conducted by Rato and colleagues (e.g., Kivistö-de Sousa, Carlet, Julkowska & Rato, 2017;Rato, 2018;Rato & Rauber, 2015;Rato, 2014;Rato et al, 2014). Therefore, we hypothesized that identical vowels /iː/ and /ɛ/ would be more easily perceived and similar L2 vowels /ɪ/ and /ae/ would be more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…English vowel sounds have been widely reported to be challenging for adult learners with different L1 backgrounds. Several studies on L2 English vowel acquisition by L1 speakers of different Romance languages with small vowel inventories such as Spanish (Aliaga-Garcia, 2010Carlet & Cebrian, 2015;Carlet, 2017;Cebrian, 2006;Cebrian, Mora & Aliaga-Garcia, 2010;Flege, Bohn, & Jang, 1997), Italian (Flege, MacKay, & Meador, 1999;Flege & MacKay, 2004) and Portuguese (Nobre-Oliveira, 2007;Rato, 2018;Rato, & Rauber, 2015;Rato, 2014;Rato, Rauber, Soares, & Lucas, 2014, Rauber, 2010Rauber, Escudero, Bion & Baptista, 2005) have revealed that the perception of the larger inventory of English L2 vowels is difficult due to an L2-to-L1 mapping issue (Bohn, 2017), that is, to how learners perceptually map the vowel sounds of the target language onto the vowel categories of the native language. Current models of L2 speech learning such as the Speech Learning Model (SLM, Flege, 1995) and Perceptual Assimilation Model (PAM-L2, Best & Tyler, 2007) propose that the perceptual similarity between L1 and L2 vowels is one of the most important predictors of difficulty/ease in L2 vowel learning, with more target-like acquisition expected to occur when the L2 sound is perceived as different to the existing L1 sounds.…”
Section: Introductionmentioning
confidence: 99%
“…he English vowel contrasts /i/-/ɪ/ and /ɛ/-/ae/ present both production and perception diiculties for adult native EP speakers. English /ɪ/ and /ae/ tend to be assimilated into the Portuguese vowel sounds /i/ and /ɛ/ respectively, and no distinction between the two vowels of each pair is made due to their acoustic and articulatory proximity (Rato, 2014;Rato et al, 2014). he L1 Catalan participants of the study spoke the Eastern Catalan variety of the language.…”
Section: Vowel Systems Of the L1s Of The Present Studymentioning
confidence: 99%